The influence of organisational justice on employees' commitment in manufacturing firms in Oyo state, Nigeria: implications for industrial social work (2015)
Economic institutionalisation of work with its attended problematic side effects like ineffectiveness, straitjacketing of workers and reduced innovation makes management look for the corollary points of sense of duty (organisational justice) as operation parameters in the workplace for greater benefits of trust and commitment of staffers. It is against this background that this study investigated the influence of organisational justice on organisational commitment in manufacturing firms in Ibadan, Oyo State, Nigeria. The descriptive survey research design of ex-post facto type was used for the study. Two hundred and fifty (250) employees were randomly selected from five manufacturing firms from Industrial Estates in Ibadan, Oyo States. The respondents span across the four major job levels from senior management, middle management, supervisory and junior staff. The main instrument used for the study was a questionnaire tagged “Organisational Justice and Organisational Commitment Questionnaire - OJOCQ” with five sub-sections. Frequency counts and percentages were used to analyse the demographic characteristics of the respondents while Pearson Product Moment Correlation and Multiple Regression Analysis were used to analyse the research questions and hypotheses at 0.05 level of significance. Findings from the study showed that the joint contribution of the independent variables to the dependent variable was significant (F = 163.165). It was found that there was significant and positive relationship between distributive justice and organisational commitment. (r = .697) Furthermore, there was significant positive relationship between procedural justice and organisational commitment (r = .739) and that there was significant positive relationship between interactional justice and organisational commitment (r = .715). It was recommended that industrial social workers should advocate on behalf of employees and ensure that management of organisations give room for fair and just procedures (procedural justice and distributive justice) coupled with proper interaction (interactional justice) so that employees will be able to give better response to the organisation in terms of commitment, positive behaviour and increased productivity.